KONSERVASI CAGAR BUDAYA KONSERVASI CAGAR BUDAYA BERBASIS KEARIFAN TRADISIONAL DI KEPULAUAN RIAU: Introduction, Method, Results and Discussion, conclusion - Anastasia Wiwik Swastiwi (Borobudur, 2022)
The Riau Archipelago keeps objects of immovable or movable cultural heritage that are scattered among its people. As one of the areas that at that time was the center of Malay civilization in the Melaka Straits area, the Riau Archipelago has a glorious historical heritage. Traces of the past are still attached to the life traditions of the Riau Archipelago Malay community. Based on the Law on Cultural Conservation Number 11 of 2010 concerning the preservation of cultural heritage which states that the preservation of cultural heritage must be carried out. One of the efforts that can be done is to preserve mobile cultural heritage in the Riau Archipelago by using traditional wisdom-based cultural heritage conservation methods. This research was conducted using a cultural approach. The results of this study produce an inventory of the traditional practices of the people of the Riau Archipelago, which have been and are being developed, which need to be developed into a method of conservation of cultural heritage based on traditional wisdom not only in the Riau Archipelago but also in various other regions in Indonesia. This inventory of traditional practices for conserving movable cultural heritage materials includes various materials such as wood, metal, fabric/textile, bamboo, light wood, porcelain, paper, stones and gemstones. While the traditional ingredients consist of lime, pineapple, cloves, cinnamon, pepper, sea water/brackish water, river water/muddy water, citronella root, vinegar water and taro leaves/taro leaves.